2020
DOI: 10.1002/bse.2510
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of perceived moral obligation and sustainability self‐identity on sustainability development: A theory of planned behavior purchase intention model of sustainability‐labeled coffee and the moderating effect of climate change skepticism

Abstract: This study sought to elucidate the antecedents that may influence the effect of people's purchase behavior on the Earth's sustainable development. It included people's perceived moral obligation and sustainability self‐identity in the theory of planned behavior (TPB) model to investigate attitudes among the Taiwanese public's attitude toward purchasing sustainability‐labeled coffee and their purchase intentions. The moderating effect of climate change skepticism is also considered in this study. A total of 745… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
5

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 87 publications
4
64
0
5
Order By: Relevance
“…For instance, consumers may believe that being ‘green’ is simply a marketing ploy to charge more. Several green purchase studies in other scenarios, for instance, have noted that ‘green scepticism’ is rising among consumers (M. F. Chen, 2020; do Paço & Reis, 2012; Leonidou & Skarmeas, 2017). Furthermore, issues like greenwashing are becoming common whereby businesses implement green services and facilities only in places where they can influence consumer perception without actually helping the green cause (H. Chen et al, 2019).…”
Section: Thematic Focimentioning
confidence: 99%
“…For instance, consumers may believe that being ‘green’ is simply a marketing ploy to charge more. Several green purchase studies in other scenarios, for instance, have noted that ‘green scepticism’ is rising among consumers (M. F. Chen, 2020; do Paço & Reis, 2012; Leonidou & Skarmeas, 2017). Furthermore, issues like greenwashing are becoming common whereby businesses implement green services and facilities only in places where they can influence consumer perception without actually helping the green cause (H. Chen et al, 2019).…”
Section: Thematic Focimentioning
confidence: 99%
“…The use of perceived moral obligation in several studies has been found to improve the predictability of one's intention and behavior regarding issues involving ethical considerations (Kurland, 1995;Lam, 1999). Perceived moral obligation (PMO) and other additional variables have been widely used in explaining consumers' green purchase intention and behavior (M. F. Chen, 2020;Petschnig, Heidenreich, & Spieth, 2014). For instance, M.-F. Chen and Tung (2014) found that the PMO positively influences consumers' green hotel visiting intention.…”
Section: Perceived Moral Obligation (Pmo) and Green Purchase Intention (Gpi)mentioning
confidence: 99%
“…En tanto, las normas subjetivas son una función de las creencias normativas personales de un individuo y su motivación para aplicarlas (Chen, 2020), además, depende de la presión que siente una persona de realizar o no una acción, en la cual la opinión de los demás influye en sus decisiones (Prakash y Pathak, 2017). En otras palabras, el comportamiento de una persona es influenciado por la aprobación de amigos, familiares, compañeros de trabajo o socios comerciales (He y cols., 2019).…”
Section: Modelo De La Teoría Del Comportamiento Planeadounclassified
“…Por su parte, Chan y Bishop (2013), mencionan que existen estudios previos que enfatizan en agregar al modelo de la TCP la variable de obligación moral, argumentando que tanto la obligación moral y las actitudes comparten correlaciones muy altas, puesto que la obligación moral ha sido considerada como un antecedente poderoso de las actitudes hacia el cuidado del medio ambiente. De igual manera, Chen (2020), expone que la obligación moral puede incrementar el poder predictivo del modelo de la TCP en el contexto de productos amigables con el medio ambiente. En tanto, Beldad y Hegner (2018), dedujeron que la adición de la obligación moral al modelo, aumentaba la varianza explicada en la intención de consumir productos verdes.…”
Section: Introductionunclassified